Serum miR-34a-5p Expression as a Potential Diagnostic Biomarker in Iraqi Women with Breast Cancer - Abbood, Alaa Saadi; Hasan, Alaa Saad; Thanoon, Allaa Hatim; Jaber Faisal, Anwer; Ahmed Saeed, Baraa (Asian Pacific Journal of Cancer Biology, 2026)
Background: MicroRNAs are small non-coding RNAs that are imperative in regulating gene translation. One of them is miR-34a-5p, which is reported to be a potent tumor suppressor, particularly in breast cancer. Aim: The research aims to examine the potential connection of the level of expression of miR-34a-5p with the clinical characteristics of older people with breast cancer tissue. Methods: RT-qPCR was used to measure levels of serum miRNA -34a -5p in 50 female breast cancer patients and 50 healthy controls. Result: Patient data, comprising body mass index, family history, hormonal profile, breast cancer (BC) type, and subtype, exhibited significant differences between the BC group (mean age 50.16 ± 10.63) and the control group (35.96 ± 11.93). There were no significant variation in miR-34a-5p expression among BC patients with respect to family history, HER2 positivity, progesterone expression, or estrogen detection (p > 0.05). However, a notable elevation in miR-34a-5p expression was noted in BC patients compared to controls (P < 0.02), with higher mean (34.03 ± 2.86 vs. 27.25 ± 5.64) and median (33.82 vs. 31.48) expression levels in the BC group. Conclusion: The findings indicate that there is a great enhancement in miR-34a-5p in the serum of older Iraqi women with breast cancer compared to the healthy controls, which implies that miR-34a-5p can serve as a non-invasive biomarker for diagnosis. Further studies are needed to explore its tumor-suppressive mechanisms and clinical utility in the prognosis or treatment of breast cancer in adult individuals.